Seismic Isolation Strategies for Earthquake-Resistant Construction : Emerging Opportunities. - Melkumyan, Mikayel (Cambridge Scholars Publishing, 2019)
Earthquakes are catastrophic events that cause huge economic losses due to the vulnerability of the existing building stock. However, collapses of vulnerable buildings can be avoided if preventative measures, such as enhancement of their earthquake resistance, are implemented on time. This book will allow the reader to become acquainted with a number of unique, modern and cost-effective seismic isolation strategies, which can be easily, and in very short periods of time, and without interruption of the use of the buildings, implemented with high efficiency in existing buildings, making them ea.